Air embolism complicating endoscopic retrograde cholangiopancreatography - Mouna Medhioub; Becem Trabelsi; Amal Khsiba; Mohamed Saied; Moufida Mahmoudi; Asma Ben Mohamed; Manel Yacoubi; Lamine Hamzaoui; Mechaal Ben Ali (Future Science OA)
Aim: Venous air embolism is a rare but potentially life threatening complication of endoscopic retrograde cholangiopancreatography. Diagnosis is difficult because of the lack of specific signs or symptoms. Case: A 62-year-old man underwent endoscopic retrograde cholangiopancreatography for choledocholithiasis. A cardiovascular collapse occurred during the procedure. The echocardiography showed air within the right ventricle. Aspiration of air from the right ventricle was done and saved the patient's life. Conclusion: We highlight through this case that increased awareness is essential for prompt recognition of the air embolism to allow life-saving therapy.